A triple comparative study of primary dendrite growth and peritectic solidification mechanism for undercooled liquid Fe59Ti41 alloy. (1st May 2017) - Wu, Y.H.; Chang, J.; Wang, W.L.; Hu, L.; Yang, S.J.; Wei, B.
Abstract: The rapid solidification kinetics of undercooled hypoperitectic Fe59 Ti41 alloy was quantitatively investigated by electrostatic levitation (ESL) and electromagnetic levitation (EML) methods combined with a high-speed photography technique. The maximum undercoolings Δ T obtained by ESL and EML methods were 200 K (0.12  T L ) and 315 K (0.19  T L ), respectively. Double recalescence processes corresponding to the primary dendrite growth and subsequent peritectic reaction were recorded at various undercoolings. The dependence of primary dendrite growth velocity V on the undercooling Δ T satisfied a double-exponential relation. A longest incubation time and a highest undercooling of peritectic reaction were experimentally determined at the same critical undercooling of about 86 K. In contrast, the peritectic reaction time decreased linearly with enhanced Δ T . As Δ T rised in ESL and EML experiments, primary Fe2 Ti phase successively appeared as well-defined coarse dendrites, greatly refined dendrites and finally evolved into a maze-like morphology composed of vermicular dendrites. Meanwhile, the layer thickness and volume fraction of peritectic FeTi phase remarkably reduced, which suggested that peritectic reaction was suppressed to some extent. The solid solubilities of Fe2 Ti and FeTi phases were significantly extended during rapid solidification. As another comparison, drop tube experiment was also conducted to explore the solidification behaviors under larger undercoolings and cooling rates. A mechanism transition of 'peritectic solidification → metastable coupled-growth between primary and peritectic phases' was observed with decreasing alloy droplet size. Graphical abstract: Image